Political conflict, prevention and management: A Nigerian experience - Saidu, Alhaji Adamu; Maidawa, Bashir Ahmed (2014)
The early economists and political punter foresaw a more promising future for Nigeria as an emerging black power but the country has now experienced its ownparcel of political upheavals due to largely lack of tolerance, compromise, good judgment and willingness to stand by the rule of law and fair play in governance, leading to political instability engulfing the nation since independence to present contemporary day.Political conflict currently radiates in almost every part of the country.This article delineates the elements that contributed to the political disputes in Nigeria and the methods use in the management and prevention of conflicts.The study conducted through established documents in current Studies that have dominated discussions on Nigerian politics and challenging crisis now experienced within the country.The paper concludes with some recommendation that proffer solutions to these problems.